THE RELATIONSHIP BETWEEN KNOWLEDGE AND PARITY WITH ANEMIA IN TRIMESTER III PREGNANT WOMEN AT PMB HJ. MURTINAWITA, SST PEKANBARU - Rini Ratih; Nurmaliza -; Yusmaharani - (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
Based on the results of basic health research, the incidence of anemia in Indonesia is still high, there are 37.1% of pregnant women who are anemic. Based on an initial survey conducted at the Pekanbaru City Health Office, from data on pregnant women number 2 in 2019, there were 2,333 people in the working area of ​​the Rejosari Health Center, Pekanbaru City. Meanwhile, in third trimester pregnant women the risk of anemia is quite high, namely 29%. Anemia events have a negative effect during pregnancy. The research objective was to determine the relationship between knowledge and parity with anemia in third trimester pregnant women. Place This research was conducted at PMB Hj. Murtinawita, SST Pekanbaru. This type of quantitative research, cross-sectional research design. With 51 Samples. Consecutive sampling technique, Nominal and Ordinal measuring scale, univariate and bivariate data processing. Based on bivariate analysis with the Chi-Square test, it shows that there is a relationship between knowledge, parity, husband's support and anemia in PMB Hj. Murtinawita, SST Pekanbaru with p value <α. Based on the results of the study, it can be concluded that there is a relationship between knowledge and parity with anemia in PMB Hj. Murtinawita, SST Pekanbaru. It is expected that health workers at the puskesmas can provide counseling about pregnancy to pregnant women regarding the risk of anemia in pregnancy and carry out early detection to prevent anemia.